2017
DOI: 10.1371/journal.pone.0178643
|View full text |Cite
|
Sign up to set email alerts
|

Linking epigenetic function to electrostatics: The DNMT2 structural model example

Abstract: The amino acid sequence of DNMT2 is very similar to the catalytic domains of bacterial and eukaryotic proteins. However, there is great variability in the region of recognition of the target sequence. While bacterial DNMT2 acts as a DNA methyltransferase, previous studies have indicated low DNA methylation activity in eukaryotic DNMT2, with preference by tRNA methylation. Drosophilids are known as DNMT2-only species and the DNA methylation phenomenon is a not elucidated case yet, as well as the ontogenetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…DNMT2 is the smallest MET gene family found in different eukaryotes. Due to the considerable variability in the specific target recognition domain, DNMT2 is also involved in RNA methylation modification (Jeltsch et al, 2017;Vieira et al, 2017). DRM is homologous to DNMT3 in mammals, and both differ only in the order of related catalytic domains (Cao et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…DNMT2 is the smallest MET gene family found in different eukaryotes. Due to the considerable variability in the specific target recognition domain, DNMT2 is also involved in RNA methylation modification (Jeltsch et al, 2017;Vieira et al, 2017). DRM is homologous to DNMT3 in mammals, and both differ only in the order of related catalytic domains (Cao et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The function of SmCMT2a remains to be elucidated. Although DNMT2 contains highly conserved C-terminal methyltransferase domain and is able to interact with type-2 histone deacetylases (AtHD2s) in Arabidopsis ( Song et al, 2010 ), its function remains largely unclear ( Goll et al, 2006 ; Ponger & Li, 2005 ; Vieira et al, 2017 ). In this study, we found that SmDNMT2 showed no differential transcript abundance in all tissues analyzed and various treatments ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the absence of DNA-methylase domain makes the DMT proteins can't normally methylate the cytosine [6,67]. All members of TaDRM (27) and TaDNMT2 (3) only contained the DNAmethylase domain. The BAH domain (Bromo Adjacent Homology) existed in almost members of TaMET1 and TaCMT.…”
Section: Structural and Evolutionary Features Of Dmt Genes In Wheatmentioning
confidence: 99%
“…Based on sequence homology, the DNMT2 was originally considered to be DNA methyltransferase. However, robust DNA methyltransferase activity could not be observed using DNMT2 preparations and the considerable variability in the target DNA sequences showed that DNMT2 enzymes were actually tRNA transferases [27][28][29].…”
Section: Introductionmentioning
confidence: 99%